Pembentukan Personal Branding Prawnche Ngaditowo melalui Media Sosial Instagram @Foodventurer_ - Tan Jaya, Thalia; Junaidi, Ahmad (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In the digital era like today, the use of social media is an activity that is loved by people of all ages. With social media, all kinds of information can be easily obtained and disseminated. The rise of food bloggers, which are increasing in number in Indonesia, makes it increasingly difficult to create a strong identity. A food blogger must have its own characteristics that distinguish it from other food bloggers and also credibility that cannot be forgotten, so personal branding activities really need to be done. This research uses a qualitative approach. This study focuses on the personal branding analysis of food blogger Prawnche Ngaditowo on the social media Instagram @foodventurer_. The conclusion that the researchers got was that Prawnche, who works as a food blogger, focuses on uploading content related to the culinary world. By becoming a well-known food blogger, Prawnche remains himself without trying to cover it up with another identity. The reviews given by Prawnche are based on honesty and truthfulness. Prawnche is also seen frequently replying to comments or interacting with his followers. This is in accordance with the theory of personal branding. Pada era digital seperti sekarang ini, penggunaan media sosial merupakan salah satu aktivitas yang digandrungi oleh masyarakat dari semua kalangan umur. Dengan media sosial, segala macam informasi dapat dengan mudah didapat dan disebarluaskan. Maraknya food blogger yang sekian banyak bertambah di Indonesia menjadikan semakin sulit menciptakan identitas yang kuat. Seorang food blogger harus memiliki ciri khas tersendiri yang membedakannya dengan food blogger lain dan juga kredibilitas yang tidak bisa terlupakan sehingga aktivitas personal branding sangat perlu dilakukan. Penelitian ini mengunakan pendekatan kualitatif. Penelitian ini memfokuskan pada analisis personal branding food blogger Prawnche Ngaditowo di media sosial Instagram @foodventurer_. Simpulan yang peneliti dapatkan adalah Prawnche yang berprofesi sebagai seorang food blogger memfokuskan dirinya untuk mengunggah konten yang berkaitan dengan dunia kuliner. Dengan menjadi seorang food blogger ternama, Prawnche tetap menjadi dirinya sendiri tanpa mencoba menutupinya dengan identitas lain. Ulasan yang diberikan oleh Prawnche berlandaskan kejujuran dan apa adanya. Prawnche juga terlihat seringkali membalas komentar-komentar atau berinteraksi dengan para pengikutnya. Hal ini telah sesuai dengan teori Personal Branding.